BENTUK PERLINDUNGAN HUKUM TERHADAP PELANGGARAN MEREK TERKENAL ASING - Margaretha Simanjuntak, Gracia; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
This paper in motivated because of the increasing number of violations foreign brands that have thepurpose of which is to determine the factors that hinder the implementation of the legal protection ofwell-known foreign trademark holders and to determine the legal safeguards against violations of foreignfamous brands. This writing method uses the normative legal method through statute approach.This paper concluded, the legal protection that inhibits the factor is the lack of information on theapplication for registration of trademark, copyright holders over the ignorance of foreign famous brandsover brand offenders and less than optimal performance of members. Preventive legal protection toprevent violations of the brand and repressive legal protection to finish the trademark infringement hasoccurred.
Keywords: Legal Protection, Infringement, Wellknown Trademarks